Histological Investigation of the Effect of the Quercetin On Methotrexate Induced Parotid Gland Injury in Rats - AK, ESİN (My University, 2022)
Methotrexate (MTX), a folic acid antagonist, is widely used as a cytotoxic agent for the treatment of some cancers and autoimmune diseases. As adverse effect, MTX also damages the cells of salivary glands and malfunction of salivary glands changes the composition and/or decreases the amount of saliva that causes dry mouth (xerostomia) presented by oral mucositis. Quercetin (Q) is a flavonoid found in fruits and vegetables and is known to be a potent anti-oxidant besides its anti-inflammatory, anti-coagulation and anti-cancer activities. This study aims to investigate the potential effect of quercetin on methotrexate induced parotid gland injury. Eighteen adult male wistar albino rats were divided into three groups. Control group (n:6): rats received saline (0.1 cc/100gr, daily) intraperitoneally (i.p.) for 5 days, Methotrexate group (MTX, n:6): rats received MTX as one single dose (20mg/kg, i.p.) on the first day of the experiment and saline (0.1 cc/100gr, i.p., daily) for 5 days. MTX + Quercetin group (MTX+Q, n:6): rats received MTX as one single dose (20mg/kg, i.p.) on the first day of the experiment and Q (50mg /kg, i.p., daily) for 5 days. At the end of the experiment, all rats were sacrificed and parotid glands were taken out for histopathological investigation. After routine light microscopic tissue process, approximately 5 μm paraffin sections were stained with hematoxylin and eosin. In MTX group, degeneration of acinar and duct cells and vasocongestion were seen. A prominent improvement in the morphology of parotid gland was observed in MTX+Q group. Our histological study revealed that quercetin treatment might have a protective effect on methotrexate induced parotid gland injury. This study was supported by Marmara University Scientific Research Projects Commission (Project No: TYL-2022-10428). Keywords: Methotrexate, Quercetin, Parotid Gland, Histology
Keywords: Methotrexate; Quercetin; Parotid Gland; Histology